Electrocardiographic changes in focal takotsubo syndrome: a case report. Issue 11 (November 2019) - Limite, Luca R.; Tini, Giacomo; Arcari, Luca; Cacciotti, Luca; Russo, Domitilla; Sclafani, Matteo; Magiotta, Ambra; Volpe, Massimo; Autore, Camillo; Musumeci, Maria B.
Abstract : Supplemental Digital Content is available in the text